Impact of Atomic Layer Deposition to Nanophotonic Structures and Devices - Saleem, Muhammad Rizwan; Ali, Rizwan; Khan, Mohammad Bilal; Honkanen, Seppo; Turunen, Jari (Frontiers in Materials, 2014)
We review the significance of optical thin films by Atomic Layer Deposition (ALD) method to fabricate nanophotonic devices and structures. ALD is a versatile technique to deposit functional coatings on reactive surfaces with conformal growth of compound materials, precise thickness control capable of angstrom resolution and coverage of high aspect ratio nanostructures using wide range of materials. ALD has explored great potential in the emerging fields of photonics, plasmonics, nano-biotechnology, and microelectronics. ALD technique uses sequential reactive chemical reactions to saturate a surface with a monolayer by pulsing of a first precursor (metal alkoxides or covalent halides), followed by reaction with second precursor molecules such as water to form the desired compound coatings. The targeted thickness of the desired compound material is controlled by the number of ALD cycles of precursor molecules that ensures the self limiting nature of reactions. The conformal growth and filling of TiO2 and Al2O3 optical material on nanostructures and their resulting optical properties have been described. The low temperature ALD-growth on various replicated sub-wavelength polymeric gratings is discussed.